2016
DOI: 10.1016/j.atherosclerosis.2016.07.925
|View full text |Cite
|
Sign up to set email alerts
|

Dyslipidaemia in the Middle East: Current status and a call for action

Abstract: The increase in the cardiovascular disease (CVD)-associated mortality rate in the Middle East (ME) is among the highest in the world. The aim of this article is to review the current prevalence of dyslipidaemia and known gaps in its management in the ME region, and to propose initiatives to address the burden of dyslipidaemia. Published literature on the epidemiology of dyslipidaemia in the ME region was presented and discussed at an expert meeting that provided the basis of this review article. The high preva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
38
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 51 publications
3
38
1
Order By: Relevance
“…In general, the pathophysiological basis for cardiovascular events is atherosclerosis, a chronic inflammatory disease closely associated with certain cardiovascular risk factors such as hypercholesterolemia, hypertriacylglyceridemia, lowering of HDL cholesterol (HDL-c), hypertension, diabetes mellitus and obesity 2 . Hypercholesterolemia, in particular, stands out for being one of the main responsible for metabolic disorders of lipids, and considered the greatest risk factor for CVD 3 . It is evident, therefore, the role of different dietary patterns on the modulation of atherosclerosis and cardiovascular risk factors, especially with regard to the presence of lipids in the diet.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, the pathophysiological basis for cardiovascular events is atherosclerosis, a chronic inflammatory disease closely associated with certain cardiovascular risk factors such as hypercholesterolemia, hypertriacylglyceridemia, lowering of HDL cholesterol (HDL-c), hypertension, diabetes mellitus and obesity 2 . Hypercholesterolemia, in particular, stands out for being one of the main responsible for metabolic disorders of lipids, and considered the greatest risk factor for CVD 3 . It is evident, therefore, the role of different dietary patterns on the modulation of atherosclerosis and cardiovascular risk factors, especially with regard to the presence of lipids in the diet.…”
Section: ■ Introductionmentioning
confidence: 99%
“…These fatty acids play important role in numerous physiological and biochemical functions in the body, and substitution of SFA by monounsaturated (MUFA) and PUFA fat sources in the diet is considered an effective strategy for the control of hypercholesterolemia and consequent reduction in the incidence of CVD. Numerous evidence also emphasize PUFA may influence the improvement of autonomic function, antiarrhythmic, decreased platelet aggregation and blood pressure, improved endothelial function, stabilization of atheromatous plaque and triacylglycerols levels 3 . Furthermore, deficiencies in these fatty acids may have various health damages 10 , especially on the cognitive function of the individual, related, for example, to the docosahexaenoic acid (DHA, 22:6 n-3) deficiency 11 .…”
mentioning
confidence: 99%
“…Middle East exhibits a high prevalence of metabolic syndrome (37), diabetes (38,39), and familial hypercholesterolaemia (40); these disorders along with the practice of consanguineous marriages has resulted in a pattern of dyslipidemia (low high-density lipoprotein cholesterol and high triglycerides) that is different from many other regions of the world (41). These lifestyle disorders have reached the proportion of public health crisis; this epidemic is primarily a consequence of recent environmental changes that have triggered the effect of pre-existing susceptibility genes via gene-environment interactions (42).…”
mentioning
confidence: 99%
“…In addition to these high prevalence rates, the profile of plasma lipid disorders observed in the Middle Eastern population differs somewhat to that seen in many other regions, with metabolic dyslipidaemia (high TG, low HDL-C and high or normal LDL-C) being one of the most common types [9]. The presentation of high TG and low HDL-C levels has also been observed among patients in the region who are already receiving chronic statin treatment; the DYSIS Middle East study (n = 2182) found that 62% still have high LDL-C levels, 56% have low HDL-C levels, and 49% have high TG levels [17].…”
Section: Introductionmentioning
confidence: 85%
“…Disorders of plasma lipids are a well-known problem in the Western world [8], and are an issue of increasing importance in the Middle East. Although estimates are hampered by a lack of clinical studies in the region and by inconsistencies in the definitions and thresholds used in those studies that have been conducted, the prevalence of plasma lipid disorders in the region is high [9]. Available data vary in their estimates [10][11][12][13][14][15][16], with prevalence as high as 50% or more in some areas.…”
Section: Introductionmentioning
confidence: 99%